Comparison of Efficiency Between Corticosteroid and Platelet Rich Plasma Injection Therapies in Patients With Knee Osteoarthritis - Ece USLU GÜVENDİ; Ayhan AŞKIN; Güven GÜVENDİ; Hikmet KOÇYİĞİT (Archives of Rheumatology, 2018)
Objectives: This study aims to assess whether platelet rich plasma (PRP) is an effective treatment for knee osteoarthritis, and compare its efficiency with corticosteroid treatment in terms of pain control, physical function, and quality of life. Patients and methods: The study included 50 patients (4 males, 46 females; mean age 61.6±6.9 years; range 50 to 75 years) who were diagnosed as grade 3 knee osteoarthritis. Patients were randomized into three groups as corticosteroid group (receiving one corticosteroid injection), single PRP group (receiving one PRP injection), and three PRP group (receiving three PRP injections with one week interval). All patients were given a home exercise program. Patients were evaluated with Visual Numeric Scale (VNS), Western Ontario and McMaster Universities Arthritis Osteoarthritis Index (WOMAC), Lequesne index and the Hospital Anxiety and Depression Scale before treatment, and at second and sixth months following the implementation of injections. Results: In single and three PRP groups; VNS, WOMAC and Lequesne scores decreased significantly at second month follow-up; also, sixth month scores showed a slight increase but remained significantly lower than baseline. In corticosteroid group, all VNS, WOMAC, and Lequesne scores decreased at second month follow-up; however, at sixth month, rest, night VNS and WOMAC stiffness scores were increased while no significant difference was found with baseline. At sixth month; VNS movement, WOMAC pain, function, and the total and Lequesne scores were worse, but remained significantly lower than baseline. When groups were compared, three PRP group’s second month VNS movement scores were significantly lower than the corticosteroid group. Sixth month VNS movement and WOMAC pain scores were significantly lower in single and three PRP groups compared to the corticosteroid group, with no significant difference between the PRP groups. Conclusion: Our findings revealed that PRP is a safe treatment option and efficient in osteoarthritis symptom control up to six months after application. Treatment response obtained with corticosteroid injection has a shorter duration than PRP treatment.